Development of Production and Investment Measures for Energy Saving and Energy Efficiency in Rural Areas - MARATOVICH, Kaparov Nurtaza; OMARKHANOVA, Zhibek; BEKARYSOVNA, Rakhisheva Aida; SAPARBAYEVA, Saulebaevna Saule; IKRAMKHANOVNA, Zakirova Dilnara; BAKYTGUL, Ainakanova (Journal of Environmental Management and Tourism, 2020)
The relevance of the research topic is that energy-saving is the key element of modern energy development in the country. In Kazakhstan, energy-saving, and improving the energy efficiency of agriculture is currently a priority task that will solve energy, environmental and economic problems. Without a solution to these problems, the country's development will inevitably hold back. The head of state in the field of energy conservation has set a goal to reduce the energy intensity of the gross domestic product by at least 25% by 2020, and annual energy-savings of 3.5% after 2020. Industry in rural areas consumes more than 70 % of all electricity. As part of the comprehensive plan, their energy audit was conducted 50/50 (50 % of the financing is the enterprises' funds, the remaining 50 % is the state budget). As a result of the energy audit, systematic measures were developed to reduce the energy intensity of the industry, including the electric power industry. Large unproductive losses of energy resources are in the private sector, in this connection, since 2019, the energy audit of JSC "Kazakhstan center for modernization and development of housing and communal services (housing and communal services)" is conducted on budget funds in the private sector. Energy conservation is one of the most important and strategic tasks of the country. Rapidly developing production requires additional energy costs. This is confirmed by the annual increase in energy tariffs. In turn, resources are not unlimited, and their irrational consumption will inevitably lead to not only economic but also to an environmental crisis.